2005
DOI: 10.1097/01.crd.0000145928.08280.ef
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Diseases in Aged Patients

Abstract: Patients with CHDs, especially those with low mortality in childhood, are more frequently reaching old age. New imaging techniques and endovascular treatments seem useful in the challenging management of CHDs in aged patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Abnormalities in development of pharyngeal arches and their arterial system during the embryonic period can lead to various aortic anomalies including CoA [ 1 ] . Although most of the cases are related with developmental abnormalities, autoimmune vasculitis syndromes and atherosclerotic processes may also be associated with adult onset atypical coarctation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in development of pharyngeal arches and their arterial system during the embryonic period can lead to various aortic anomalies including CoA [ 1 ] . Although most of the cases are related with developmental abnormalities, autoimmune vasculitis syndromes and atherosclerotic processes may also be associated with adult onset atypical coarctation.…”
Section: Discussionmentioning
confidence: 99%
“…Coarctation of the aorta (CoA) is a congenital cardiovascular anomaly that typically occurs within the vicinity of the ductus arteriosus. It has a prevalence of four in 10,000 live births [ 1 , 2 ] . Most of CoA cases are congenital, and the acquired form of the disease is rare.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested excellent long-term results with reduction in arrhythmias, pulmonary hypertension, and paradoxical cerebral embolism after ASD closure at young age [1]-[2]. Over the past years, an increasing number of elderly patients (age > 60 years) have been admitted for transcatheter closure to prevent ongoing congestive heart failure from volume overload.…”
Section: Introductionmentioning
confidence: 99%